Analysis of Physico-Mechanical Properties of Jute and Polyester Blended Yarn - Dip, Tanvir Mahady; Begum, Prof. Dr. Hosne Ara; Hossain, Md. Abdullah Al; Uddin, Md. Mazbah; Faruque, Md. Omar (International Journal of Scientific Research and Management (IJSRM), 2018)
The cardinal objective of blending is to combine fibers which emphasizes good quality and minimizes poor quality. Jute is a natural fiber popularly known as the golden fiber of Bangladesh. It is one of the cheapest and strongest natural fibers and is considered the fiber for the future. Polyester is a manufactured product which tends to be very resilient, quick drying, resistant to biological damage such as mold and mildew, easy to wash and able to hold forms well. Although polyester is often maligned as a textile, it has many useful applications. The following study is an experimental research on how blending of Polyester with Jute behaves a single yarn manufactured using jute yarn manufacturing machineries. Tossa Jute of B grade and Polyester of 1.4 Denier & 32 mm staple length were chosen for the blending. The blending was performed at the 2nd Draw Frame stage of jute manufacturing system and blending ratio of jute and polyester fibers is 80:20. Count of Jute blended sliver and yarn after each stage was measured and recorded. The present work is concerned with the investigation of physical properties of manufactured jute blended yarns. Tests were conducted on blended yarn to find out Count, Twist per Inch (TPI), Strength, Quality Ratio Moisture Regain, Moisture Content, Hairiness, Percentage of Fibers in the final blended yarn etc.